Idarucizumab: Clinical Role of a Novel Reversal Agent for Dabigatran - Teleb, Mohamed; Salire, Kevin; Wardi, Miraie; Alkhateeb, Haider; Said, Sarmad; Mukherjee, Debabrata (Cardiovascular & Haematological Disorders - Drug Targets, 2016)
Atrial fibrillation (AF), a common cardiac arrhythmia associated with increased risk of heart failure, thromboembolic phenomena and death, is a leading cause of hospitalization of adults. A major complication of AF is an increased risk of ischemic stroke leading to long-term disability and in severe cases, death. Historically, Coumadin has been the drug of choice for chronic anticoagulation and stroke prevention in AF patients however, given the need for constant monitoring and multiple drug interactions, newer anticoagulants have been developed. One such drug is dabigatran, with the promise of less frequent monitoring and decreased bleeding tendencies as compared to Coumadin. The main disadvantage of dabigatran has been the lack of a reversal agent in case of severe bleeding or emergent surgical intervention. This was until the recent The Food and Drug Administration approval of idarucizumab, a potential reversal agent for dabigatran. In this article, we discuss the evidence addressing idarucizumab safety, tolerability and its efficacy for reversing effect of dabigatran.
Keywords: reversal agent